Pathology of Bolivian Hemorrhagic Fever in the Rhesus Monkey - Terrell, Timothy G. (1973)
Gross and microscopic lesions associated with Bolivan hemorrhagic fever virus infection in the rhesus monkey were studied in 10 animals which died following inoculation. Gross lesions included skin rash, lymphadenopathy, splenomegaly, meningeal edema, hydropericardium and enlarged friable livers. Hemorrhagic manifestations of the infection were not consistently observed, but hemorrhages were present in the skin, heart, brain and nares in some monkeys. Histopathologic lesions were fairly consistent. Hepatic necrosis with the presence of acidophilic hyaline bodies, necrotizing enteritis, epithelial necrosis and adrenal cortical necrosis were present in all monkeys. Those monkeys which died after the seventeenth day of infection had nonsupurative meningoencephalitis; lymphoid necrosis was present in 3 monkeys that died after day 18. Other microscopic lesions included myocardial degeneration, lymphoid and reticuloendothelial cell hyperplasia and lymphoid depletion. Most of the histopathologic lesions described in human autopsy material were reproduced; however, the necrosis in the skin and oral mucosa, mucosa of the gastrointestinal tract and the adrenal cortex have not been described in man. Despite these apparent discrepancies the results of this investigation indicate that the rhesus monkey is a good experimental model for the study of Bolivian hemorrhagic fever infection.